2018
DOI: 10.5114/aic.2018.76405
|View full text |Cite
|
Sign up to set email alerts
|

Two-year clinical outcomes after implantation of an everolimus-eluting bioresorbable scaffold (Absorb) in stable angina and acute coronary syndrome patients. Single-centre real-life registry data

Abstract: AimThe aim of this long-term registry data was to evaluate 2-year clinical and angiographic outcomes after implantation of everolimus-eluting bioresorbable scaffolds (Absorb) from the Latvian Centre of Cardiology Real-life Registry.Material and methodsBetween November 2012 and December 2014 in the Centre of Cardiology Real-life Bioresorbable Vascular Scaffold Registry, 187 patients with stable angina or acute coronary syndrome and available 2-year follow-up were selected. All patients had percutaneous coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Of note, none of these studies was powered for this endpoint. The rates of target vessel myocardial infarction in these studies were in the range of 5.5–7.3%, again not outside a hypothetical confidence interval of the registries by Orlik et al [ 4 ] and Briede et al [ 6 ]. Finally, their rate of scaffold restenosis was in line with another registry recently published that reported in a similar cohort a rate of 6% at 2 years and 9% at 3 years [ 17 ].…”
supporting
confidence: 45%
See 2 more Smart Citations
“…Of note, none of these studies was powered for this endpoint. The rates of target vessel myocardial infarction in these studies were in the range of 5.5–7.3%, again not outside a hypothetical confidence interval of the registries by Orlik et al [ 4 ] and Briede et al [ 6 ]. Finally, their rate of scaffold restenosis was in line with another registry recently published that reported in a similar cohort a rate of 6% at 2 years and 9% at 3 years [ 17 ].…”
supporting
confidence: 45%
“…Given the small sample size and fortunately low incidence of scaffold thrombosis, a comparison with the results of these larger trials is impossible. In the study by Orlik et al [ 4 ], no thrombosis was observed; in the study by Briede et al [ 6 ], only two such events had been observed at 2 years (1.1%). In the Absorb II trial, the rate of scaffold thrombosis was 1.5%; in the ABSORB III and AIDA trials the rates of scaffold thrombosis were 1.9% and 3.5%.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The CVD was defined as fatal IS, fatal MI, or other CVD (i.e., any sudden or unexpected death unless proven as non-cardiovascular on autopsy). The relationship between new onset angina and coronary status was established with coronary angiography in order to ensure coronary lesion progression, and exclude symptoms related to stenosis recurrence (restenosis or stent thrombosis as related to different mechanisms) [17, 18]. For further analysis only new angina due to CLP was taken into account.…”
Section: Methodsmentioning
confidence: 99%